Risk Based Strategic Alignment in Higher Education: Governance, Digital Transformation, and Sustainability Outcomes - Akhmad, Noor; Nitiasih, Putu Kerti; Herawati, Nyoman Trisna; Riastini, Putu Nanci (LITPAM, 2026)
Higher education institutions increasingly operate in digital environments that require stronger integration among governance, risk management, digital transformation, and sustainability outcomes. However, the literature on strategic risk, digital governance, artificial intelligence adoption, cybersecurity, learning analytics, and institutional sustainability in higher education remains dispersed across different research streams. This article aims to synthesize the literature on risk-based strategic alignment as a mechanism linking governance, digital transformation, and sustainability outcomes in higher education. The study employed a systematic literature review using the PCC framework and a narrative-integrative thematic synthesis approach. The Scopus search identified 96 records. After database filtering, 62 records were excluded, 34 reports were sought for retrieval, 14 reports were not retrieved, 20 reports were assessed for eligibility, and 10 studies were included in the main synthesis. The findings reveal five major patterns: strategic risk in higher education is multidimensional; governance mechanisms serve as the main instruments for risk-based alignment; digital transformation functions both as an institutional enabler and as a source of risk; sustainability outcomes are more frequently represented through resilience, responsible artificial intelligence, educational equity, and sustainable digital education than through direct sustainability performance indicators; and no dominant theoretical model has yet consolidated the relationship among these domains. The study concludes that risk-based strategic alignment offers an integrative lens for understanding how higher education institutions connect risk visibility, governance capacity, digital transformation, and sustainability-oriented outcomes.